Indefinite presidential re-election and the erosion of constitutionalism in Latin America: a critical reflection (Revista revoluciones, 2026)
Indefinite presidential reelection has become one of the main drivers of the erosion of constitutionalism in Latin America, by allowing the executive branch to use formal legal mechanisms to weaken democratic alternation and subordinate systems of checks and balances. As a study objective, the focus was on the dynamics of democratic regression in Latin America, concentrating on the role of constitutional courts and tribunals (CCs) regarding reforms that allow indefinite presidential reelection. This phenomenon was studied through the jurisprudential analysis of key constitutional rulings, which made it possible to identify common patterns of judicial interpretation aimed at legitimizing the concentration of power. Through a comparative study of rulings and omissions in Nicaragua, Honduras, Bolivia, El Salvador, Venezuela, and Ecuador, it was evaluated how the judicialization of politics becomes a mechanism of constitutional authoritarianism, allowing the concentration of executive power. Empirically, the comparative analysis made it possible to identify common patterns of legalized authoritarianism that studies focused on a single country tend to perceive as exceptional or contextual, showing that, despite ideological differences and historical trajectories, executives resort to almost identical legal repertoires to perpetuate themselves in power. It is concluded that the instrumentalization of the doctrine of political rights (Art. 23 ACHR) to invalidate entrenched clauses is the legal vehicle for this regression.
Keywords: hyper-presidentialism; unlimited re-election; democratic backsliding